Preparing for the Attack: Mitigating Risk through Routines in Armed Self-Defense - Barnhart,Michelle; Huff,Aimee; McAlexander,Brandon; McAlexander,Jim (Journal of the Association for Consumer Research, 2018)
Prior research has shown that owning firearms for self-defense can be motivated by perceived risks and a desire to mitigate those risks. Keeping and carrying guns for self-defense also introduces risks to owners and others. We examine ways that consumers mitigate these latter risks. We employ theories of practice and prior work on risky consumption to interpret observational, interview, and textual data gathered from a multi-sited ethnography of consumers of handguns for self-defense. We reveal that these consumers attempt to mitigate risks in three ways: through readiness practices with guns but no assailant, simulated scenario practices incorporating simulated assailants, and mental rehearsals incorporating imagined assailants. This research contributes a model of risk mitigation in risky consumption, explicates how social norms and mental activities foster a sense of security from specific risks, and shows that collaboration is required for development of practical understanding of risk-mitigating routines that incorporate multiple people.
Keywords: Marketing